Science for policy: The need for a Commission for Science - Hendy, Shaun (New Zealand Science Review, 2016)
There is growing interest in the use of scientific research for informing public policy (Gluckman, 2011). Science has shown itself increasingly able to make predictions of catastrophic harms many decades in advance, as well as suggesting ways in which these harms may be avoided. Scientific methodologies are now also being drawn on in many other areas of policy. Randomised controlled trials (RCT) and related statistical and experimental techniques are starting to be used to evaluate the effectiveness of existing policy and to experiment with the development of new policies, for instance (Pearce & Raman 2014). More recently, government itself has become an important source of scientific knowledge, and it is likely to become even more important in the coming decades. In New Zealand the Integrated Data Infrastructure (IDI) has become a unique and powerful source of socio-economic data that captures many aspects of the lives of residents and citizens (Statistics New Zealand 2016). The IDI is used by independent researchers, as well as by researchers within government agencies such as the Ministry of Social Development, to inform operational practice and public policy, as well as to study the effectiveness of these policies. Indeed, the Ministry of Social Development has built a substantial data science team which carries out re-search commissioned by its policy branch (Ministry of Social Development 2016). Scientific research, however, requires more than just data and skilled researchers who can apply appropriate statistical techniques to this data. Modern science needs to be practised under the open scrutiny of other researchers to function effectively (Miguel et al. 2014). Peer review, for instance, while still necessary, is no longer regarded as sufficient to correct scientific fraud (Stroebe et al. 2012). Furthermore, the public increasingly has expectations that the conduct of scientific research be open to their scrutiny as well (Yarborough 2014). As a result, a need has been identified for new institutions for the governance of evidence-based policy making (Pearce & Raman 2014). In this article I propose a Parliamentary Commission for Science, an organisation that would be responsible for ensuring the scientific use of evidence by government and fostering corresponding levels of trust in the public.